Pengaruh Produksi, PDB, dan Nilai Tukar terhadap Ekspor Karet Indonesia ke Korea Selatan - Kurniawaty Kurniawaty; Zamzami Zamzami; Nurhayani Nurhayani (Jurnal Ekonomi Aktual, 2022)
This study analyzes the effect of rubber production, GDP, and the exchange rate on Indonesia's exports to South Korea. The data used is secondary data in the form of time series data from 2002 to 2018. The data comes from Gapkindo, the Central Bureau of Statistics, and Bank Indonesia. Data were analyzed using multiple regression models. The analysis found that during the period 2002 to 2018, the average growth in rubber export volume was 9.2% per year, production was 5.4% per year, South Korea's GDP was 3.0% per year, and the exchange rate was 2.5%  per year. South Korea's GDP significantly affects Indonesia's rubber exports to South Korea, while rubber production and the exchange rate have no significant effect.